Comparative Analysis of Digital and Conventional Learning Media: The Impact on the Student Learning Outcomes - Sutarto, Sutarto; Hendrilia, Yudi; Judijanto, Loso; Arsyad, Muhammad; Lestari, Nana Citrawati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the comparative effects of digital learning media and conventional learning media on student learning outcomes and engagement. The method used in this research is an experimental design with two groups, each using digital and conventional learning media. The study was conducted in several schools in Semarang City, with a sample of 11th-grade students divided into two experimental groups. Data was collected through knowledge tests (pre-test and post-test), student engagement questionnaires, and direct observation. The results show that the group using digital media experienced a more significant improvement in learning outcomes (an average increase of 20.1 points) compared to the conventional group (14.7 points). Additionally, the digital group also showed a higher level of engagement, both based on the questionnaire (score 4.2 vs. 3.6) and observation results (4.5 vs. 3.2). In conclusion, the use of digital learning media is more effective in improving learning outcomes and student engagement compared to conventional learning media, suggesting that technology should be more integrated into the learning process.